Optimal Occupant Kinematics and Crash Pulse for Automobile Frontal Impact - Zhiqing Cheng; Joseph A. Pellettiere; Jeff R. Crandall; Walter D. Pilkey (Shock and Vibration)
Based on a lumped-parameter model of the occupant-vehicle system, optimal kinematics of the occupant in frontal impact are investigated. It is found that for the minimization of the peak occupant deceleration, the optimal kinematics move the occupant at a constant deceleration. Based on this the optimal vehicle crash pulse is investigated. The optimal crash pulse for passive restraint systems is found to be: a positive impulse at the onset, an immediate plunge followed by a gradual rebound, and finally a positive level period. The relation of the peak occupant deceleration to the impact speed, crash deformation, and vehicle interior rattlespace is established. The optimal crash pulse for active and pre-acting restraint systems is discussed.